Examining of teacher candidates' attitudes to science teaching and self-efficacy related to alternative measurement assessment - Ugras, Mustafa; Ay, Kemalettin; Altunbas, Seda; Cil, Erol (Elsevier Science Bv, 2012)
The purpose of this study, determine the pre-service science and classroom teachers' attitudes towards science teaching and self-efficacy perceptions related to alternative measurement assessment that based upon constructivism. The participants of this research included teacher candidates who were fourth year students in 2011-2012 academic years majoring in Science and Class Teaching Programmers at Firat University and Erzincan University, Faculty of Education, in Turkey. In this descriptive study, the attitude toward science teaching scale which was designed by Thomson and Shrigley and adopted to Turkish by Ozkan, Tekkaya and Cakiroglu and self efficacy scale related alternative measurement assessment that developed by Buldur were used as data collecting tools. From the examination of obtained data, we can say that both groups of pre-service science teachers have positive attitudes toward science teaching in general terms. However: statistically significant difference was found between attitudes of pre-service science teachers and class teachers. These results show that the pre-service science teachers have more positive attitudes toward science teaching than pre-service class teachers.
Cyprus International Conference on Educational Research (CY-ICER) -- FEB 08-11, 2012 -- Middle E Tech Univ No Cyprus Campus, CYPRUS
Keywords: Science Education; alternative measurement assessment; Teacher attitude; Teacher self-efficacy